Association of Epidemiologic Factors and Genetic Variants Influencing Hypothalamic-Pituitary-Adrenocortical Axis Function With Postconcussive Symptoms After Minor Motor Vehicle Collision. Issue 1 (January 2016) - Auvergne, Lauriane; Bortsov, Andrey V.; Ulirsch, Jacob C.; Peak, David A.; Jones, Jeffrey S.; Swor, Robert A.; Domeier, Robert M.; Lee, David C.; Rathlev, Niels K.; Hendry, Phyllis L.; McLean, Samuel A.
ABSTRACT: Objectives: To determine the influence of epidemiologic factors and the influence of genetic variants affecting FKBP5, a protein known to modulate hypothalamic-pituitary-adrenocortical axis function, on the severity of somatic symptoms commonly termed "postconcussive" 6 and 12 months after motor vehicle collision (MVC). Methods: European Americans 18 to 65 years of age who presented to one of eight emergency departments (EDs) after MVC were enrolled. Exclusion criteria included hospital admission. Blood samples were collected in the ED for genotyping. Participants completed evaluations including an adapted Rivermead Post-Concussive Symptoms Questionnaire in the ED and at 6 weeks, 6 months, and 1 year. Repeated-measures analysis of covariance was used to evaluate the association between epidemiologic factors (sociodemographic, pre-MVC health, collision characteristics, head injury, peritraumatic pain, and stress), FKBP5 genetic variants, and postconcussive symptom severity. Results: Among 943 patients recruited in the ED, follow-up was completed on 835 (88%) at 6 months and 857 (90%) at 1 year. Self-reported head impact during collision was not associated with chronic postconcussive symptom severity. After correction for multiple testing, three FKBP5 single-nucleotide polymorphisms (rs3800373, rs7753746, and rs9380526) predicted chronic postconcussive symptom severity, with an average symptom severity of 1.10 (95% confidence interval = 0.96–1.24), 1.36 (1.21–1.51), and 1.55 (1.23–1.88) for one, two, or three copies of minor allele at rs3800373 ( p = .001). Similar effect sizes were observed for the minor alleles of rs7753746 and rs9380526. Conclusions: Postconcussive symptoms after minor MVC are not generally related to the severity of mild brain injury. This study shows that neurobiologic stress systems may play a role in the pathogenesis of postconcussive symptoms. Abstract : Supplemental digital content is available in the text.